Knowledge management in E-learning practices - (:unkn) unknown (My University, 2012)
Thanks to extension of IT in educational activities, the difficulties based on time and space are disappearing and the management and the execution of these activities can be implemented more effectively and beneficially. Even though there are significant developments about e-learning both in academic and professional platforms, there are some main questions that must be considered like: How can e-learning and knowledge management be integrated? Do these present e-learning systems fulfill the requirements of knowledge management? Are provided facilities from these systems being utilized in knowledge management accurately? In this paper, firstly e-learning, and then knowledge and knowledge management concepts are considered with their major points. In the next section it is considered that how e-learning systems can be integrated with knowledge management; under the subjects of knowledge management models, system features, and requirements of knowledge management. © The Turkish Online Journal of Educational Technology.
Keywords: E-learning; e-learning systems; Integration; Knowledge management